The Role of Brain-Reactive Autoantibodies in Brain Pathology and Cognitive Impairment - Mader, Simone; Brimberg, Lior; Diamond, Betty (Frontiers in Immunology, 2017)
Antibodies to different brain proteins have been recently found to be associated with an increasing number of different autoimmune diseases. They need to penetrate the blood brain barrier in order to bind antigens within the central nervous system (CNS). They can target either neuronal or non-neuronal antigen and result in damage either by themselves or in synergy with other inflammatory mediators. Antibodies can lead to acute brain pathology, which may be reversible; alternatively, they may trigger irreversible damage that persists even though the antibodies are no longer present. In this review we will describe two different autoimmune conditions and the role of their antibodies in causing brain pathology. In Systemic Lupus Erythematosus (SLE), patients can have double stranded DNA antibodies that cross react with the neuronal N-methyl-D-aspartate receptor (NMDAR) which have been recently linked to neurocognitive dysfunction. In Neuromyelitis Optica (NMO), antibodies to astrocytic aquaporin-4 (AQP4) are diagnostic of disease. There is emerging evidence that pathogenic T cells also play an important role for the disease pathogenesis in NMO since they infiltrate in the CNS. In order to enable appropriate and less invasive treatment for antibody-mediated diseases we need to understand the mechanisms of antibody mediated pathology, the acute and chronic effects of antibody exposure, if the antibodies are produced intrathecally or systemically, their target antigen and what triggers their production. Emerging data also show that in utero exposure to some brain reactive antibodies, such as those found in SLE can cause neurodevelopmental impairment since they can penetrate the embryonic blood brain barrier. If the antibody exposure occurs at a critical time of development this can result in irreversible damage of the offspring that persists throughout adulthood.